Demand Distribution Dynamics in Creative Industries: the Market for Books in Italy - Edoardo Gaffeo; Antonello E. Scorcu; Laura Vici (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
We study the distribution dynamics of the demand for books in Italy. We find that for each of three broad sub-markets in which the book publishing industry can be classified - Italian novels, foreign novels and essays - sales over a three-year sample can be adequately fitted by a power law distribution. Our results can be plausibly interpreted in terms of a model of interactions among buyers exchanging information on the books they buy.
Keywords: 330